Revision of Eulasia genei Truqui, with description of Eulasia rittneri n. sp. from Israel and synonymic notes on related species (Coleoptera: Scarabaeoidea: Glaphyridae) - Uliana, Marco; Sabatinelli, Guido (Zootaxa, 2010)
This paper presents a revision of the species Eulasia genei Truqui, 1848. A total of 773 specimens, including all type series of the involved taxa, were examined. Nominal species currently in synonymy with E. genei are discussed. All the current synonyms proved to be wrongly attributed, and the following new synonyms are proposed: Eulasia pretiosa Truqui, 1848 = E. genei chaifensis (Reitter, 1890) = E. japhoensis (Petrovitz, 1972). Eulasia hybrida agricola (Reitter, 1890) is no longer considered a synonym of E. genei Truqui and Amphicoma genei ab. nobilissima Balthasar, 1929 is an unavailable name. Eulasia rittneri n. sp., a species close to and parapatric to E. genei, is described and illustrated. The diagnostic characters are discussed in relation to their discriminating value, with special consideration for the morphology of the aedeagus. A technique for observing the volumetric shape of the endophallus has been modified and used for the first time as such for the study of Scarabaeoidea. On the basis of the large number of specimens gathered, the distribution range of both species is defined and notes on their ecology and phenology are presented.